Autonomia delle persone in movimento e antropologia compromessa: riflessioni sulle reciproche influenze nella gestione dell’immigrazione in Perù - Irene Palla (Archivio Antropologico Mediterraneo)
Immigration in Peru is a highly recent and accelerated phenomenon that has completely changed the country’s politics, society, and economy since 2017, and the pandemic for Covid-19 has exacerbated it. Its management is a privileged observation field for the analysis of the interactions between new and old local and international actors on narratives, practices, and hierarchies of power. The anthropologist recognizes herself as part of this process. She explores the more or less intentional mutual influence between the subjects of the shelters, her figure, and the ethnography produced between September 2020 and March 2022. Entering into the Latin American debate and placing it in dialogue with the concept of 'other meaning' by Ferdinando Fava, the text questions the contribution of compromised anthropology to the critical reflection of studies on the autonomy of migrations, highlighting the peculiarities of Peru. The author proposes a diachronic analysis – before, during, and after the field –, and she reflects on the assumption of different professional roles, not exclusively universitarian. The arthicle examines the approaches (methodology of closeness and participatory definition of the object of study), the dynamics and advocacy actions that, both academically and politically, have led to the emergence of voices, claims, and silent practices for the recognition of the rights and struggles of people on the move in the State and internationally.